Using the Juvenile Sex Offender Assessment Protocol–Revised to Assess Psychopathy: A Preliminary Investigation: - Wijetunga, Charity (Criminal justice and behavior, 2018)
Assessment of sexual and nonsexual recidivism risk is important for juveniles who have offended sexually (JSOs). It is unclear whether clinicians who assess risk for both types of recidivism should use a JSO-specific measure alone or in combination with an assessment of other potential risk factors, such as psychopathy. Using a sample of 72 JSOs, this study examined the reliability and validity of a scale (Scale P) intended to assess psychopathic traits comprised of seven items from the Juvenile Sex Offender Assessment Protocol-Revised (J-SOAP-II). Scale P demonstrated adequate internal consistency and was significantly correlated with the Hare Psychopathy Checklist-Youth Version (PCL:YV). In addition, Scale P significantly predicted nonsexual and sexual recidivism as well as the PCL:YV and was a significantly stronger predictor of nonsexual recidivism than several of the preexisting J-SOAP-II scales. These preliminary findings suggest that Scale P may enhance the clinical utility of the J-SOAP-II.